The meaning of Hitler [videorecording (DVD)] - Epperlein, Petra; Tucker, Michael; Tucker, Michael; Tucker, Michael; Amis, Martin; Bauer, Yehuda; Haffner, Sebastian (IFC Films, 2022)
"A provacative interrogation of our culture's fascination with Hitler and Nazism is set against the backdrop of the current rise of white supremacy, the normalization of anti-Semitism and the weaponization of history itself. Shot in nine countries, the film traces Hitler's movements, his rise to power, and the scenes of his crimes as historians and writers, and famed Nazi hunters Beate and Serge Klarsfeld weigh in on the lasting impact of his virulent idealogy."--